The Effectiveness of Inversion In Drying Arabika Coffee Manually and Mechanically In East Java, Indonesia - Julio Pratama, Agief; Prananda, Intan; Wiraguna, Edi (Devotion : Journal of Research and Community Service, 2025)
Post-harvest coffee processing such as drying can affect the effectiveness of the processing process, which in turn will affect the quality of the coffee beans. The process involves male and female workers who have different techniques and working times. The study aimed to compare the effectiveness of manual and mechanized coffee drying and the effect of worker gender on manual drying. The study was conducted from August to November 2023 in East Java, Indonesia. The sampling method used a drying floor of 4 floors with a drying floor area of 490 m2 and time measurements were carried out 4 times repeating each reversal method. The results showed that mechanical reversal was more efficient with an average time of 19.48 minutes compared to the manual method. The gender of the workers showed a significant effect on the reversal of coffee drying and the reversal method affected the weight loss of arabica coffee.